2009
DOI: 10.1007/s00167-009-0891-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative treatment of degenerative posterior root tear of the medial meniscus

Abstract: We reviewed thirty patients with degenerative posterior root tear of the medial meniscus to investigate clinical results of non-operative treatment retrospectively. There were 3 men and 27 women at a median age of 59 years old (range, 51-65). The median follow-up period was 36 months (range, 24-51). Non-operative treatments included non-steroidal anti-inflammatory drugs daily for 8-12 weeks and supervised physical therapy twice a week at least during a period of 8 weeks. The symptoms, physical signs, the Visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 17 publications
(31 reference statements)
2
62
0
3
Order By: Relevance
“…Nevertheless, the clinical results of MMPRT treatment can be satisfying with early diagnosis and proper conservative treatment. Lim et al33) compared clinical outcomes of non-operative treatment, either drug therapy or physiotherapy, that was prescribed to 30 patients for 8 weeks. At an average of 36 months of follow-up, the authors found a statistically significant enhancement in both groups when compared to the placebo group.…”
Section: Treatment Of Mmprtmentioning
confidence: 99%
“…Nevertheless, the clinical results of MMPRT treatment can be satisfying with early diagnosis and proper conservative treatment. Lim et al33) compared clinical outcomes of non-operative treatment, either drug therapy or physiotherapy, that was prescribed to 30 patients for 8 weeks. At an average of 36 months of follow-up, the authors found a statistically significant enhancement in both groups when compared to the placebo group.…”
Section: Treatment Of Mmprtmentioning
confidence: 99%
“…Lim et al [9] reported a successful conservative treatment of MMRT; however, most patients were acute onset and the follow-up period was only 12 months. Recent biomechanical studies reported that repaired MMRT restored the peak contact pressure close to the normal level [6][7][8]10].…”
Section: Introductionmentioning
confidence: 98%
“…3,[5][6][7] Recently, surgeons have recognized the importance of MMPRTs, and several biomechanical and biological studies have considered what type of management is most appropriate. Several regimens for MMPRTs have been introduced, including conservative treatment, 8,9 meniscectomy, 10,11 root refixation, [11][12][13][14][15][16] and high tibial osteotomy. 17 The "traditional" treatment for MMPRTs is meniscectomy; it has been widely used for a long time.…”
mentioning
confidence: 99%